PURCHASING DECISION OF IPHONE: THE ROLE OF PRODUCT QUALITY, BRAND IMAGE AND E-WOM - Kuswibowo, Christian; Widodo, Anung; Santoso, Agus; Pujianto, Hendri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to analyze the impact of The Influence of Product Quality and Brand Image on Purchase Decisions for iPhone Cell Phone Products Using Word of Mouth as an Intervening Variable. Iphone users in Tangerang City are the subjects of this study. The study was conducted with 175 respondents using quantitative descriptive methods. The sample length uses a purposeful sampling method that pays special attention to finding patterns. The survey method used when collecting data using a questionnaire tool. The analytical method used in this research is the Component or Variance Based Structural Equation Model where the data processing uses the Partial Least Square (Smart-PLS) program version 3.2.8 PLS. This study proves that product quality has a positive and significant effect on electronic word of mouth, brand image has a positive and significant effect on electronic word of mouth, product quality had a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions and electronic word of mouth had a positive and significant effect on purchasing decisions.